Implementation of safety measures to counter a driver’s drowsiness - Zillur, Sheikh Faiyadh; Tasfia, Faiza Zahin; Zaman, Srejoni; Sumaya, Atoshe Islam (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.